Two Faces of Disaster Response: Transcending the Dichotomy of Control and Collaboration during the Nepal Earthquake Relief Operation. Issue 3 (November 2016) - Wolbers, Jeroen; Ferguson, Julie; Groenewegen, Peter; Mulder, Femke; Boersma, Kees
In the aftermath of the devastating earthquakes in Nepal, a large scale humanitarian response was launched. We studied the response operation four weeks after the last quake, using participant observations and interviews. Our findings indicate that the response operation was characterized by two faces: control and collaboration. These are rooted in governance models of chaos, command and control, versus continuity, coordination and collaboration. Using the case of Kathmandu Living Labs, we show how during the first phase of the response formal humanitarian organizations gradually pushed aside important grassroots initiatives. In the second phase, we analyse how the government sought to take control of the response by formally ending the relief phase, having regained itself after the shock of the first impact. Drawing on these results, we theorize consequences for network governance, and identify a new governance mode that transcends the dichotomy between control and collaboration: net-centric governance.